The effect of spinning parameters and fiber blending ratio on the physical properties of pineapple leaf fiber (PALF)-cotton yarns - Zolkifflee, Nurul Husna; Roslan, Mohd Nazrul; Abdul Halip, Juliana; Kamarudin, Khairu; Shaari, Muhammad Farid; Aziz, Asna Nabilah (Universiti Putra Malaysia Press, 2024)
Pineapple leaf fiber (PALF) is known as pineapple residue and has potential as a textile material. Typical yarn manufacturing adopts ring spinning technique, yet it is challenging for course fibers, including PALF. PALF has been used in clothing and paper production using textile thread. It has the highest modulus among leaf fibers, comparable to synthetic fibers such as aramid and glass, and possesses the greatest tensile strength among leaf fibers. PALF has high fineness index makes it ideal for industrial yarn and woven fabric applications. Using natural fibers offers benefits such as being environmentally friendly, cost-effective, and lightweight yet sturdy. This study evaluates the physical properties of PALF-cotton yarn at three twist speeds, two total drafts, and three PALF-cotton blending ratios. The methodology of this study involves carding, drawing, and ring spinning of the PALF-cotton fibers. The process starts with cutting and opening PALF before blending it with cotton fiber using a carding machine. The finding shows that the average diameter and fineness values range from 205 μm to 458 μm and 31.2 to 67.0 tex, respectively. The study also reported that twist speed, total draft, and blending ratio affect the diameter and fineness of the yarns. In contrast, the increment of twist speed and total draft decreases the fineness and diameter of PALF-cotton yarns. Pineapple leaf fiber (PALF) shows great potential in the apparel industry. Three regression models were presented to predict the future ring-spinning process, and pineapple waste can be repurposed into valuable products, reducing overall waste.